Stock of Dwellings, House Prices and Interest Rates: An Econometric Model for the UK - Y.C. Tse, Raymond (International Journal of Property Sciences (E-ISSN: 2229-8568), 2008)
The often volatile behaviour of UK housing stocks is analysed in an annual econometric model. Theory suggests that an increase in house prices leads to a rise in housing stock, whereas an increase in interest rates leads to a decrease in housing stock. This paper develops an econometric model to examine the cyclical activity of stocks of dwellings in the UK. The use of annual data allows us to analyse the period 1964-96. The paper also examines the time series behaviour of housing stocks, house prices and interest rates in the UK market. The evidence presented in this paper supports the predictions of theory. The presence of adjustment costs suggests that the adjustment of housing stocks is inelastic with respect to house prices. Keywords: Housing stock; interest rates; house prices; unit root tests